Los estilos de afrontamiento y el estrés por la sobrecarga de los cuidadores de un miembro familiar con discapacidad, en usuarios del proyecto: atención en el hogar y la comunidad dirigido a personas con discapacidad del municipio del cantón Francisco de Orellana, provincia de Orellana, período 2015 - Camacho Yunga, Karina Maricela (2015)
The purpose of this study was to analyze the relationship between coping styles and the stress by overload of the caregivers of a family member with disabilities, in project users of home care and community. Descriptive study, of cross-sectional cut; the methods used were: the scientific, analytical, synthetic, deductive, inductive, the questionnaire was applied of coping ways (Lazarus and Folkman), the scales to assess the level of stress and overload of the caregiver (Zarit) in a sample of 150 caregivers relatives who have family members with disabilities. Results: 84.67% they use a coping low level of self-control and 76% manifest a high level of responsibility; 74.67% expressing the intense overload, 50% of caregivers have passed the limit of stress Existing relationship between coping styles and the stress by overload that maintain the caregivers of a family member with disabilities. Conclusions: Most caregivers faced with low self-control but with accepting responsibility, reaching extreme limits by intense stress overload.